Information Systems Outsourcing 2009
DOI: 10.1007/978-3-540-88851-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology Workforce Skills: The Software and IT Services Provider Perspective

Abstract: It is now commonplace for an organization to turn to external firms for the provision of IT services and software. As technology advances and the business environment continues to evolve, a key challenge facing IT software and service providers is identifying critical skill sets, both today and in the future. The challenge is compounded as a result of the continuing growth of outsourcing and the increasing demand for technology solutions. This paper explores that challenge through a survey of IT software and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 22 publications
4
32
0
2
Order By: Relevance
“…These findings extend and reinforce the message that IT professionals are expected to possess both non-technical and technical skills and that their choices are "not either/or but both" [3, p. 114]. Furthermore, preliminary findings of a follow-up study with IT software and service providers indicate that these same skills are important for all IT professionals [6,7].…”
Section: The Case For a Varied Set Of Skillssupporting
confidence: 68%
“…These findings extend and reinforce the message that IT professionals are expected to possess both non-technical and technical skills and that their choices are "not either/or but both" [3, p. 114]. Furthermore, preliminary findings of a follow-up study with IT software and service providers indicate that these same skills are important for all IT professionals [6,7].…”
Section: The Case For a Varied Set Of Skillssupporting
confidence: 68%
“…It involves the planning, organizing, controlling the project, and managing project risk, in order to meet the project objectives within various time and budget constraints (R. Chan & Rosemann, 2001;Goles, Hawk, & Kaiser, 2008). Reich (2007) refers to this as process knowledge in her research.…”
Section: Project Management Knowledgementioning
confidence: 99%
“…They state that this knowledge is more important and has a greater impact on project success than application domain and development method knowledge. Research done by Goles et al (2008) has found that project management skills and knowledge are one of the highest ranked skills for IT firms today.…”
Section: Project Management Knowledgementioning
confidence: 99%
“…As such, OOSD projects involve challenges and risks that are not encountered (at least to the same extent) in the other remote sourcing models. The primary challenge is the combining of team members from two or more companies-which may have very different organizational rules, working practices, operational systems, and governance structures-into an effective team [26].…”
Section: Related Conceptsmentioning
confidence: 99%